2021
DOI: 10.3892/etm.2021.9651
|View full text |Cite
|
Sign up to set email alerts
|

Schizandrin B attenuates hypoxia/reoxygenation injury in H9c2 cells by activating the AMPK/Nrf2 signaling pathway

Abstract: Schizandrin B exhibits prominent antioxidant and anti-inflammatory effects, and plays an important role in ameliorating myocardial ischemia/reperfusion injury. However, the underlying protective mechanisms remain to be elucidated. The aim of the present study was to explore the cardioprotective effects of schizandrin B against hypoxia/reoxygenation (H/R)-induced H9c2 cell injury, focusing on the role of the adenosine monophosphate-activated protein kinase (AMPK)/nuclear factor erythroid 2-related factor 2 (Nrf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…A previous study reported that Galanthamine improves myocardial I/R induced cardiac dysfunction by activating the AMPK/Nrf2 pathway in rats [ 29 ]. Galanthamine improves myocardial I/R-induced cardiac dysfunction by activating AMPK/Nrf2 pathway in rats [ 28 ]. Galanthamine improves myocardial I/R-induced cardiac dysfunction by activating the AMPK/Nrf2 pathway in rats [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study reported that Galanthamine improves myocardial I/R induced cardiac dysfunction by activating the AMPK/Nrf2 pathway in rats [ 29 ]. Galanthamine improves myocardial I/R-induced cardiac dysfunction by activating AMPK/Nrf2 pathway in rats [ 28 ]. Galanthamine improves myocardial I/R-induced cardiac dysfunction by activating the AMPK/Nrf2 pathway in rats [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine monophosphate-activated protein kinase (AMPK), a silk/threonate albuminase composed of three peptide chains, is an important regulator of human energy metabolism and is closely related to promoting catabolism, inhibiting anabolism, improving endothelial function, alleviating inflammatory response, and inhibiting oxygen-reduction reaction [26,27]. It has been shown in previous studies that AMPK can activate Nrf2 through phosphorylation and generate downstream antioxidant genes such as HO-1 and NQO1 to play an antioxidative stress role [28]. Here, we found that PF induced the A previous study reported that Galanthamine improves myocardial I/R induced cardiac dysfunction by activating the AMPK/Nrf2 pathway in rats [29].…”
Section: Discussionmentioning
confidence: 99%
“…The cardioprotective effect of schisandrin B was also shownon H9c2 cardiomyocytes (rat embryonic cardiomyoblasts) in myocardial ischemia-reperfusion injury (MIRI) model through attenuation of the oxidative stress and inflammatory response via the AMPK/Nrf2 signaling pathway. Mechanistically, schisandrin B pretreatment reversed hypoxia/reoxygenation (H/R)-induced iROS generation, higher MDA content, upregulation of Keap1 and decreased enzymatic activities of SOD and GPx but induced the downregulation of pro-inflammatory cytokines (IL-1β, TNF-α and IL-8) and the upregulation of the anti-inflammatory cytokine IL-10 [ 50 , 51 ]. In another study, schisandrin B effectively protected the heart from injury caused by a doxorubicin analog pirarubicin by exerting strong antioxidant capacity [ 137 ].…”
Section: Lignans With Antioxidant and Anti-inflammatory Actionmentioning
confidence: 99%
“…The inhibition of AMPK reduced the anti-inflammation effects of Schisandrin B on NLRP3 inflammasome. Zhao et al suggested that Schisandrin B attenuates hypoxia/reoxygenation injury by activating the AMPK/Nrf2 signaling pathway [ 54 ]. Thus, Schisandrin B induced AMPK/Nrf2 signaling pathway to suppress NLRP3 inflammasome in model of colitis by the inhibition of ROS-induced mitochondrial damage.…”
Section: Discussionmentioning
confidence: 99%